Monazite trumps zircon: applying SHRIMP U–Pb geochronology to systematically evaluate emplacement ages of leucocratic, low-temperature granites in a complex Precambrian orogen - Piechocka, A.; Gregory, C.; Zi, J.; Sheppard, S.; Wingate, M.; Rasmussen, Birger (Springer, 2017)
Although zircon is the most widely used geochronometer to determine the crystallisation ages of granites, it can be unreliable for low-temperature melts because they may not crystallise new zircon. For leucocratic granites U–Pb zircon dates, therefore, may reflect the ages of the source rocks rather than the igneous crystallisation age. In the Proterozoic Capricorn Orogen of Western Australia, leucocratic granites are associated with several pulses of intracontinental magmatism spanning ~800 million years. In several instances, SHRIMP U–Pb zircon dating of these leucocratic granites either yielded ages that were inconclusive (e.g., multiple concordant ages) or incompatible with other geochronological data. To overcome this we used SHRIMP U–Th–Pb monazite geochronology to obtain igneous crystallisation ages that are consistent with the geological and geochronological framework of the orogen. The U–Th–Pb monazite geochronology has resolved the time interval over which two granitic supersuites were emplaced; a Paleoproterozoic supersuite thought to span ~80 million years was emplaced in less than half that time (1688–1659 Ma) and a small Meso- to Neoproterozoic supersuite considered to have been intruded over ~70 million years was instead assembled over ~130 million years and outlasted associated regional metamorphism by ~100 million years. Both findings have consequences for the duration of associated orogenic events and any estimates for magma generation rates. The monazite geochronology has contributed to a more reliable tectonic history for a complex, long-lived orogen. Our results emphasise the benefit of monazite as a geochronometer for leucocratic granites derived by low-temperature crustal melting and are relevant to other orogens worldwide.